2023
DOI: 10.3390/nano13030536
|View full text |Cite
|
Sign up to set email alerts
|

Defining Quality Criteria for Nanoplastic Hazard Evaluation: The Case of Polystyrene Nanoplastics and Aquatic Invertebrate Daphnia spp.

Abstract: Polystyrene nanoparticles are the most investigated type of nanoplastics in environmental hazard studies. It remains unclear whether nanoplastic particles pose a hazard towards aquatic organisms. Thus, it was our aim to investigate whether the existing studies and data provided therein are reliable in terms of data completeness. We used the example of Daphnia spp. studies for the purpose of polystyrene nanoplastic (nanoPS) hazard evaluation. First, a set of quality criteria recently proposed for nanoplastic ec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 66 publications
(99 reference statements)
0
3
0
Order By: Relevance
“…Most studies have been conducted on the exposure of marine organisms to commercial PS NPs purchased from authorized institutions or polyethylene terephthalate (PET) NPs. This is because PS NPs have been detected in the marine environment [80] and PET is the most widely used material for manufacturing bottles and packaging [81,82]. Few studies have been dedicated to investigating the effects of NPs released into drinking water sources on human health.…”
Section: Methodsmentioning
confidence: 99%
“…Most studies have been conducted on the exposure of marine organisms to commercial PS NPs purchased from authorized institutions or polyethylene terephthalate (PET) NPs. This is because PS NPs have been detected in the marine environment [80] and PET is the most widely used material for manufacturing bottles and packaging [81,82]. Few studies have been dedicated to investigating the effects of NPs released into drinking water sources on human health.…”
Section: Methodsmentioning
confidence: 99%
“…Numerous research papers have demonstrated the uptake of NPLs and their aggregates by various zooplankton species through both waterborne and foodborne exposure [79][80][81][82][83]. Among these species, daphnids have been extensively studied [84], particularly Daphnia magna, which constituted 79% of the studied cases, followed by Daphnia pulex (18%), and Daphnia galeata (3%) [85]. Daphnia sp.…”
Section: Npls Interactions With Freshwater Zooplankton Speciesmentioning
confidence: 99%
“…serve as filter feeders and act as primary consumers, forming a crucial link between primary producers and higher trophic levels in freshwater ecosystems [86]. Studies have examined both "apical endpoints"-including mortality/immobility, growth, feeding and egestion, swimming behavior, reproduction, embryonic development, body adsorption-and mechanistic endpoints such as oxidative stress, detoxification, immune-related processes, neurotoxicity, energy metabolism, heart rate, changes in gut epithelium, and processes related to moulting [85].…”
Section: Npls Interactions With Freshwater Zooplankton Speciesmentioning
confidence: 99%